Dynamic fragmentation analysis of potential rockfall hazards at Zixia hydropower dam, Qinghai-Tibet Plateau - Maolin Wu; Gang Luo; Xiewen Hu; Yuzhang Bi; Yufeng Wang; Ning Ma (Journal of Rock Mechanics and Geotechnical Engineering, 2025)
The fragile and intricate geological environment of the Qinghai-Tibet Plateau gives rise to numerous precarious rocks along the riverbanks, posing significant risks for the upcoming construction of hydropower stations. In order to identify potential rockfalls that could endanger the Zixia hydropower project, a comprehensive analysis employing various methods was conducted to investigate the kinematic characteristics and dynamic fragmentation of such precarious rocks. Initially, UAV oblique photography and field survey were used to create a digital elevation model with a resolution of 0.25 m and map the spatial distribution of precarious rocks. Subsequently, the development characteristics of joints within rock masses were analyzed through an adit investigation. Following these preliminary steps, a transportation simulation utilizing RocPro3D, considering stochastic initiation orientation, was employed to predict the trajectories of 18 precarious rocks. As a result, two hazardous rocks that pose a direct threat to the cofferdam were identified. Finally, considering the influence of internal structure planes, a discrete element method was applied for accurately simulating the kinematic characteristics and dynamic fragmentation of these hazardous rocks. The findings underscore several key observations: (1) Slope-parallel structure planes within these hazardous rocks play a pivotal role in both the progressive failure during initiation and dynamic fragmentation during transportation; (2) Hazardous rocks III-1 and IV-1 would pose a direct threat to the cofferdam. Notably, block b4 from hazardous rock III-1, could potentially impact the cofferdam with an energy of 4598.65 kJ and an impact force of 3007.5 kN; and (3) Continuous collisions encountered during transportation facilitate the disintegration of rock masses along structure planes and generate substantial high-velocity fragments. Finally, to cope with the impact risk of collapsing blocks, a reinforced retaining wall as the mitigation measure is recommended.